Effect of simulating training of the fundamentals of laparoscopic surgery on the attitude of operating room nurses students: an intervention study - Mohebbi Reza; Fereidouni Armin; Hannani Sedigheh; Teymoori Esmaeil (Sciendo, 2024)
Clinical education plays a key role in preparing students for patient care. Laparoscopy is one of the most important minimally invasive surgeries (MISs) wherein surgical technologists are responsible for camera navigation and assistant surgeons are responsible for peg transfer. Therefore, it is necessary to improve the attitude of the operating room students toward these skills during their study period. The present study was conducted to determine the effect of simulating training in the fundamentals of laparoscopic surgery (FLS) on the attitude of the operating room students.